2021
DOI: 10.21744/lingcure.v6ns1.2050
|View full text |Cite
|
Sign up to set email alerts
|

Organizational culture as moderating the influence of internal control and community participation on fraud prevention in village fund management during the COVID-19 pandemic

Abstract: The purpose of this study was to examine organizational culture in moderating the influence of internal control and community participation on fraud prevention in managing village funds during the covid-19 pandemic. The sample of this study was 27 villages in the province of Bali with 3 villages in each district/city having the highest Village Fund Direct Cash Assistance, so that there were 161 respondents. Data collected using a questionnaire. The data analysis technique used the Partial Least Square (PLS) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
1
10
0
4
Order By: Relevance
“…Associated with the problem of fraud, one of the factors that can prevent fraud is an organizational culture that is honest and has a professional commitment in carrying out its duties accompanied by the principles of prudence, thoroughness, and accuracy guided by standards and regulations so as to minimize fraudulent actions that occur. It is concluded that the higher the professionalism of the internal auditors reinforced by the organizational culture, the better the fraud prevention efforts that can be done (Putra et al, 2021;Nazarova et al, 2021;Jancowicz-Pitel, 2019).…”
Section: H4: Organizational Culture Strengthens Independence On Fraud Preventionmentioning
confidence: 99%
“…Associated with the problem of fraud, one of the factors that can prevent fraud is an organizational culture that is honest and has a professional commitment in carrying out its duties accompanied by the principles of prudence, thoroughness, and accuracy guided by standards and regulations so as to minimize fraudulent actions that occur. It is concluded that the higher the professionalism of the internal auditors reinforced by the organizational culture, the better the fraud prevention efforts that can be done (Putra et al, 2021;Nazarova et al, 2021;Jancowicz-Pitel, 2019).…”
Section: H4: Organizational Culture Strengthens Independence On Fraud Preventionmentioning
confidence: 99%
“…The findings are validated from the participants (Lähdevirta et al, 1988;. (Putra et al, 2021;Melnychuk et al, 2021).…”
Section: Resultsmentioning
confidence: 72%
“…The results of this study are in line with statements by (Ozigbo, 2013), (Duke, 2021), (Shepherd et al, 2011) and (Nahar & Nigar, 2018) that the presence of a positive organizational culture will be able to reduce the bystander effect, thereby reducing the tendency financial statement fraud. Similarly, the results of research by (Putri et al, 2022) (Putra et al, 2021), that a positive organizational culture will strengthen the prevention of fraud.…”
Section: Organizational Culture Moderates the Influence Of The Bystan...mentioning
confidence: 92%
“…If the opposite happens, the company does not implement positive organizational culture behavior, it will fail to prevent fraud (Duke, 2021) because negative organizational culture behavior shows the real perceived failure of the company (Shepherd et al,2011), it will strengthen the presence of the bystander. Organizational culture is a variable that can strengthen or weaken the tendency to prevent fraud, a positive organizational culture will strengthen the prevention of fraud, whereas a negative organizational culture will weaken the prevention of fraud (Putri et al, 2022) (Putra et al, 2021).…”
Section: Organizational Culture Moderates the Influence Of The Bystan...mentioning
confidence: 99%
See 1 more Smart Citation